2018
DOI: 10.1515/cclm-2017-0782
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of serum gelsolin and Gc globulin in sepsis – a pilot study

Abstract: Both serum GSN and Gc globulin may have predictive values in sepsis. Considering the small sample size of our study, further measurements are needed to evaluate our results. Measurement of Gc globulin and GSN maybe useful in assessment of sepsis severity and in therapeutic decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…According to a recent study, both serum GSN and Gc-globulin have potential as predictors of sepsis severity and sepsis-associated mortality. This study also confirmed that the pGSN concentration was higher in sepsis survivors than in non-survivors [ 105 ].…”
Section: Alterations In Plasma Gelsolin Concentrations In Differensupporting
confidence: 83%
“…According to a recent study, both serum GSN and Gc-globulin have potential as predictors of sepsis severity and sepsis-associated mortality. This study also confirmed that the pGSN concentration was higher in sepsis survivors than in non-survivors [ 105 ].…”
Section: Alterations In Plasma Gelsolin Concentrations In Differensupporting
confidence: 83%
“…It can reduce the aggregation of amyloid beta and rescue the memory deficits of AD mice [ 32 ]. The lower plasma concentration of GC is correlated with a higher risk of multiple organ dysfunction [ 33 ], septic shock [ 34 ], and in-hospital mortality [ 35 ]. However, until now, no studies have explored the role of GC in the pathophysiology of SAE.…”
Section: Discussionmentioning
confidence: 99%
“…GSN can buffer the toxic side effects of actin released from damaged tissues and can protect the body from excessive inflammatory reactions during the pathological process of septicopyemia. 2 , 9 , 10 The series of pathologic changes in urosepsis patients will damage the cells. A high amount of actin is released into the blood, and GSN in the blood is consumed gradually.…”
Section: Discussionmentioning
confidence: 99%